2009
DOI: 10.2522/ptj.20080214
|View full text |Cite
|
Sign up to set email alerts
|

Delaying Mobility Disability in People With Parkinson Disease Using a Sensorimotor Agility Exercise Program

Abstract: This article introduces a new framework for therapists to develop an exercise program to delay mobility disability in people with Parkinson disease (PD). Mobility, or the ability to efficiently navigate and function in a variety of environments, requires balance, agility, and flexibility, all of which are affected by PD. This article summarizes recent research identifying how constraints on mobility specific to PD, such as rigidity, bradykinesia, freezing, poor sensory integration, inflexible program selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 80 publications
1
107
0
9
Order By: Relevance
“…It is a complement to other rehabilitation methods and may be used by physiotherapists as well as occupational or speech therapists. Physical abilities, like weight shifting, rising from a chair, postural stability with secondary tasks and sequences of action as well as kinaesthetic awareness are practiced through rhythmic, reciprocal movements, all of which are suggested by King and colleagues [25]. The method is mentioned in the Swedish National Guidelines for Stroke [26] and there are a few small theses that show positive effects on mobility, speech fluency and quality of life in patients with stroke.…”
Section: Music As Therapy Has Been Used For Many Years As An Alternatmentioning
confidence: 99%
“…It is a complement to other rehabilitation methods and may be used by physiotherapists as well as occupational or speech therapists. Physical abilities, like weight shifting, rising from a chair, postural stability with secondary tasks and sequences of action as well as kinaesthetic awareness are practiced through rhythmic, reciprocal movements, all of which are suggested by King and colleagues [25]. The method is mentioned in the Swedish National Guidelines for Stroke [26] and there are a few small theses that show positive effects on mobility, speech fluency and quality of life in patients with stroke.…”
Section: Music As Therapy Has Been Used For Many Years As An Alternatmentioning
confidence: 99%
“…Emery et al [16] reported that Pilates training program was effective in improving core strength and posture as well as certain aspects of scapula and upper trunk displacement during a shoulder flexion task [16]. They reported that their results could support the use of the Pilates method in the prevention of neck-shoulder disorders.…”
Section: Discussionmentioning
confidence: 60%
“…The effects of Pilates exercises were investigated in the literature for many illnesses [14][15][16][17] In chronic low back pain disability scores improvement were reported by Donazelli et al [14] and by Rydeard et al [15]. Emery et al [16] reported that Pilates training program was effective in improving core strength and posture as well as certain aspects of scapula and upper trunk displacement during a shoulder flexion task [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the recent decade, a number of clinical studies have also begun to investigate the effectiveness and feasibility of specific types of physical activity intervention. These intervention types include: amplitudespecific training (ie, LSVT BIG), [21][22][23][24] rhythmic dance training (ie, tango), 25,26 functional This paper will aim to highlight strategies to encourage physical activity in PD patients, the effects of physical activity and exercise on the quality of life of individuals with PD, identify types of physical activity most recently and thoroughly supported by research and literature, and identify common barriers to participating in physical activity and ways to overcome barriers that may hinder participation in physical activity through the different stages of PD. …”
Section: Introductionmentioning
confidence: 99%